The impact of shariah voluntary disclosure: evidence from Malaysia banking institutions / Maizura Meor Zawawi …[et al.] - Meor Zawawi, Maizura; Abdul Rahman, Rahayu; Zaini, Naimah; Mahmud, Nurfarizan Mazhani (2012)
To date, there is relatively few research studies conducted to examine the zakat accounting practices in the annual financial reports of banking institutions. !r fact, the issues of zakat have attracted many arguments among Islamic scholars and public. With the emergent of Islamic financial institutions worldwide, Muslirr. community has demanded for an establishment of an accounting body to develop a set of accounting standards that adhere to Shariah, hence AAOIFI was established. MOIFI has introduced standards on zakat, namely FAS 9. In the context of Malaysia, there is an urgent need to harmonize the zakat accounting practices on companies or institutions because of their diverse practices. The effort of MASS to issued FRS-i 1 and technical release TR-i 1 on zakat has been considered as commendable efforts. The purpose of having these standards and guideline is to standardize the recognition, measurement, presentation and disclosure of a corporation's zakat. In view of this point, this study attempts to examine the extent of zakat accounting practices on compliance of these standards and guideline through examining the zakat disclosure in the annual report of Islamic financial institutions. To examine the actual disclosure practices of Islamic banks in Malaysia, a content analysis. A content analysis will be conducted to examine the actual practices of Islamic banks in Malaysia. The annual reports for firm-years 2008 and 2009 are selected. . The year 2009 was selected because the year has been the most recent available as at to date. The comparison of two (2 ) firm-years is to look at the consistency of reporting. (Ahmad Nadzri 2009, Badri 2005) The data in the annual report then will be scrutinized by comparing it with the disclosure index. For the purpose of this study, the disclosure index will be developed from the study conducted by Ahmad Nadzri (2009). The results of disclosure scoring are transformed into a format and divided into several tabulation sections for analysis process. In addition to this, a descriptive analysis based on the information which is disclosed in the annual report will be performed